Air pollution, weather, and agricultural worker productivity - Hill, Alexandra E.; Bayham, Jude; Burkhardt, Jesse; Ford, Bonne; O'Dell, Katelyn (American Journal of Agricultural Economics, 2024)
Outdoor agricultural workers often work in harsh environmental conditions, including high temperatures and poor air quality. This paper studies how these factors impact worker productivity, which can have implications for worker health, well-being, and income as well as farm payroll, production, and profitability. Our analysis uses 6 years of payroll records of harvesters on two large farms combined with pollution and weather monitor data from multiple sources. We address simultaneity issues by exploring pollution measurements from nearby upwind and downwind monitors and incorporating an alternative PM2.5 measure that better captures ambient or regional concentration. Across all specifications, results suggest that heightened concentrations of ground-level ozone and PM2.5 are associated with reduced productivity. In our main specification, we find that one standard deviation increases in ozone and PM2.5 are associated with reductions in productivity of 2% and 1.1%, respectively.
Keywords: Ozone; Particulate Matter; Temperature; Agricultural Productivity